Financial Aspects of The Company's Pricing Policy on Foreign Markets - Wojciech GRZEGORCZYK (Communications of International Proceedings, 2023)
The aim of the article is to indicate the role of financial factors (forms of payment) in the pricing policy of a company that enters international export aid markets. The forms of payment used in exports, which should secure payment for exported products, have been presented. This is important because the proceeds from sales determine the implementation of the marketing strategy and survival on foreign markets. Factoring and forfaiting are particularly convenient for the exporting company, apart from letters of credit and collection. Both of these forms of payment are used by Polish enterprises and are mainly offered by banks. Factoring is used much more often, the turnover of which is systematically growing. Forfaiting, on the other hand, refers mainly to the purchase of export receivables secured by promissory notes or letters of credit with deferred payment. It is rarely used. In addition, information on forfaiting turnover is available only in the financial documents of banks offering this service and at clients' as assignments of receivables or proper factoring. This makes it impossible to obtain precise information on the scale of forfaiting used by Polish enterprises.
Keywords: Marketing strategy on international markets; Forms of payment in export; forfaiting; factoring